Social Media Strategy Approach - Zainul Wasik; Muchammad Saifuddin; Dedy Iswanto (PT. Mawadaku Sukses Solusindo, 2025)
This article aims to investigate two main areas: first, to examine the reasons for businesses to create brand pages on social media, as well as their use, tactics and policies, and the expected outcomes; second, how users benefit from these pages, as seen from the company's perspective. In this study, a qualitative research methodology was applied. Initial evidence of the steps taken by their organizations was obtained through face-to-face interviews with 15 marketing managers who oversee their companies' social media presence. activities, including initial evidence of the steps taken by businesses, the reasons behind their involvement, and the results achieved. The main activities of the companies included prize competitions, announcements of new goods and services, fan interaction, provision of useful information, and customer support. With fans, offering useful guidance and information, and handling complaints from customers. The main forces behind this trend were the growing influence of social media, the existence of rivals, strategies from the head office, and the need to save expenses. Engaging with customers, fostering a relationship with them, raising brand recognition, and promoting customer engagement advertising goods and services, and acquiring new clients. The main expected outcomes for the firms were stated to be higher sales and more focused client acquisition. Given the qualitative character of the study and the developing area of social media research, the findings of this investigation should be regarded as preliminary and exploratory in nature, since the social media environment in which they are being refined is still being worked out. Interviewing companies from other industries and social media users would yield a more thorough comprehension of the topic. This essay offers suggestions for social media management strategies as well as some opportunities for business managers. Given the growing importance and penetration of social media in business, this article provides an exploration of how businesses can use social media content.